2003
DOI: 10.1046/j.1365-2419.2003.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the vertical distribution of eggs of anchovy (Engraulis encrasicolus) and sardine (Sardina pilchardus)

Abstract: Understanding and modelling the vertical distribution of fish eggs in the water column is a major challenge for future use of underway‐continuous egg samplers as estimators of the total egg abundance. This study presents modelling of field data of anchovy (Engraulis encrasicolus) and sardine (Sardina pilchardus) egg vertical distribution obtained from LHPR sampling in the Bay of Biscay. Starting from Sundby's model [Deep‐Sea Res.30 (1983) 645], improvements were achieved through successive modifications concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(80 citation statements)
references
References 10 publications
6
73
0
1
Order By: Relevance
“…Coombs (1981) introduced the density gradient column (DGC) to measure the neutral buoyancy of fish eggs. Subsequently, models for many species have been developed using the DGC (Boyra et al, 2003;Coombs et al, 1985;Haug et al, 1986;Tanaka, 1990), with some limitations linked to limited biological knowledge (Goarant et al, 2007).…”
Section: The Importance Of the Buoyancy Of Fish Eggsmentioning
confidence: 99%
“…Coombs (1981) introduced the density gradient column (DGC) to measure the neutral buoyancy of fish eggs. Subsequently, models for many species have been developed using the DGC (Boyra et al, 2003;Coombs et al, 1985;Haug et al, 1986;Tanaka, 1990), with some limitations linked to limited biological knowledge (Goarant et al, 2007).…”
Section: The Importance Of the Buoyancy Of Fish Eggsmentioning
confidence: 99%
“…The results will then be comparable to the Eulerian finite-volume approach used by Ådlandsvik et al (2001) and Boyra et al (2003), and has the advantage that it can be used as a component in a wider particle-tracking or individualbased framework.…”
Section: Introductionmentioning
confidence: 60%
“…Christensen et al 2007, this Theme Section), and the vertical distribution of fish eggs (e.g. Ådlandsvik et al 2001Ådlandsvik et al , Boyra et al 2003. Such studies can be done in the Eulerian framework, which models the density of tracers as it evolves in time, or in the Lagrangian or individual-based framework, which adds single particles or individuals to a numeric model of the ocean and tracks their motion.…”
Section: Introductionmentioning
confidence: 99%
“…The LHPR is a vertical sampler that was towed at 2.5 knots in an oblique haul (Boyra et al, 2003;Coombs et al, 2004), and from which a series of samples was taken every 1-2 min. LHPR includes number of eggs per stages for a number of depths independently.…”
Section: Comparison Of Different Incubation Temperature Estimates (Lhmentioning
confidence: 99%
“…On the one hand, there is no unique modal depth for the egg vertical distribution. For instance Sundby (1983) and Boyra et al (2003) found surface peaks of egg distribution for high salinity areas, and sub-surface peaks with low salinity. On the other hand, the incubation temperature of all the eggs found at the station has likely not been constant throughout the whole development of the eggs.…”
Section: Introductionmentioning
confidence: 99%